2023
DOI: 10.3390/computation11020038
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Social Media on Knowledge of the COVID-19 Pandemic on Bangladeshi University Students

Abstract: This study aimed to examine the role and impact of social media on the knowledge of the COVID-19 pandemic in Bangladesh through disseminating actual changes in health safety, trust and belief of social media’s coverage statistics, isolation, and psychological numbness among students. This study used a cross-sectional design in which a quantitative approach was adopted. Data from an online survey were collected in a short period of time during the early stages of COVID-19 to determine the relationship between s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Using exploratory factor analysis (EFA) and path analysis, the authors indicated that social media are changing the perspective of health problems, affording information and advice on undesired effects of SARS-CoV-2 infections, favoring psychological wellness, and having a beneficial effect on quarantine or lockdown. This interesting work indicated that social media are pivotal in improving knowledge about current and future pandemic conditions [1]. Examining the media's contribution to the COVID-19 pandemic in more detail, Yakunin and colleagues investigated the mass media influence in relation to the COVID-19 global health emergency, considering that this situation is an excellent example of a time when the media are crucial for educating the public about essential information.…”
Section: Socioeconomic Impact Epidemiology Diffusion and Dynamics Of ...mentioning
confidence: 99%
“…Using exploratory factor analysis (EFA) and path analysis, the authors indicated that social media are changing the perspective of health problems, affording information and advice on undesired effects of SARS-CoV-2 infections, favoring psychological wellness, and having a beneficial effect on quarantine or lockdown. This interesting work indicated that social media are pivotal in improving knowledge about current and future pandemic conditions [1]. Examining the media's contribution to the COVID-19 pandemic in more detail, Yakunin and colleagues investigated the mass media influence in relation to the COVID-19 global health emergency, considering that this situation is an excellent example of a time when the media are crucial for educating the public about essential information.…”
Section: Socioeconomic Impact Epidemiology Diffusion and Dynamics Of ...mentioning
confidence: 99%
“…Notwithstanding the challenges and lack of preparedness that educators, administrators, and institutions have encountered, a newfound openness to innovation and new forms of education has emerged. If previously, innovation and the quality of higher education were assessed by some scholars and practitioners based on the quantity of published articles in fundamental science and technology, indexed, for instance, in Web of Science (Hasanli & Shabanov, 2018), since 2019, researchers have increasingly shifted their focus to technological innovations in the pedagogical process (Wu & Liu, 2021, Chowdhury et al, 2023. Educators across all grade levels and settings felt the need to rethink their roles and ways of supporting students' learning tasks.…”
Section: Introductionmentioning
confidence: 99%